Are there employment and income gains of a national breast cancer screening program? - Zornitza Kambourova; Adriaan Kalwij (Health Economics Review, 2022)
Background: The Dutch national breast cancer screening program invites women aged 50-75 for screening. By detecting the disease in an early phase, the program aims to achieve lower breast cancer mortality and improve breast cancer survivors' health. Arguably, the latter also improves the employability of diagnosed women. Objective: This study investigates the effects of the Dutch national breast cancer screening program on diagnosed women's employment and income. Methods: The empirical analysis uses data of 229,357 women aged 40-59, of whom 10,515 were diagnosed with breast cancer at an age in the range 47-53. A regression-based difference-in-differences estimator is used to identify program effects by comparing outcomes for women diagnosed at ages 47-49 with the outcomes for those diag- nosed at ages 50-53. The empirical models account for individual fixed effects, and for age and year fixed effects by using a control group of women who were not diagnosed with breast cancer. Results: Women's employment rates declined in the six-year period after a breast cancer diagnosis with, on average, about 3 percentage points and their incomes declined with, on average, about 5% over this period. The empirical evidence, based on a comparison of outcomes for women diagnosed at ages 47-49 with the outcomes for those diagnosed at ages 50-53 when covered by the breast cancer screening program, does not support that these declines in employment and income were affected by the program. The evidence also does not support short or medium-term survival gains of the program. Conclusions: The findings of this study suggest that the Dutch national breast cancer screening program yields no discernible short or medium-term employment and income gains for women diagnosed with breast cancer.
Keywords: I10; I18; J21; J31; 330; Breast Cancer; Employment; Income; Mortality; Screening Program